2007
DOI: 10.2139/ssrn.978908
|View full text |Cite
|
Sign up to set email alerts
|

S,s Pricing in a General Equilibrium Model With Heterogeneous Sectors

Abstract: We study the impact of two-sided nominal shocks in a simple dynamic, general equilibrium (S,s)-pricing macroeconomic model comprised of heterogeneous sectors. The simple model we develop has a number of appealing empirical implications; it captures why some sectors of the economy have systematically more flexible prices, the smooth dynamics of aggregate output following a monetary shock, and a degree of price asynchronization. Incorporating multiple sectors is central to arriving at these three results.JEL Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…We note, however, that several aspects of the decomposition of the dilepton spectrum (primordial, thermal and freeze-out components) and of the fireball evolution are still a matter of debate. 46,135,154 The dropping mass scenario is found to be incompatible with the NA60 data. 148,153 The decisive role of high baryon densities for the observed medium modifications is convincingly demonstrated in Fig.…”
Section: Heavy-ion Experimentsmentioning
confidence: 83%
See 2 more Smart Citations
“…We note, however, that several aspects of the decomposition of the dilepton spectrum (primordial, thermal and freeze-out components) and of the fireball evolution are still a matter of debate. 46,135,154 The dropping mass scenario is found to be incompatible with the NA60 data. 148,153 The decisive role of high baryon densities for the observed medium modifications is convincingly demonstrated in Fig.…”
Section: Heavy-ion Experimentsmentioning
confidence: 83%
“…16 (bottom) shows the acceptance of CERES for dileptons relative to the full phase space. 143,135 Fig . 17 shows a comparison of e + e − invariant-mass spectra measured in p+Be at 450 GeV 144 and Pb+Au collisions at 158 AGeV 145 , respectively, after subtracting the combinatorial background.…”
Section: Heavy-ion Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent NA60 experiment at the CERN SPS has measured the invariant mass spectrum of low-mass dimuon pairs [1,2,3] in In-In collisions. It was seen that a large excess remained after subtracting contributions from expected hadronic (the cocktail) decays.…”
Section: Introductionmentioning
confidence: 99%
“…More recently the NA60 collaboration has released acceptance corrected transverse mass spectrum [4] of the resulting dimuon yields in different mass windows. It was found that the spectrum has a shape atypical of radial flow with a significant mass dependence suggesting that the different mass regions are populated by different sources.…”
Section: Introductionmentioning
confidence: 99%